Photomechanical responses in Drosophila photoreceptors - Hardie, Roger C.; Franze, Kristian (Science, 2012)
Phototransduction in Drosophila microvillar photoreceptor cells is mediated by a G protein-activated phospholipase C (PLC). PLC hydrolyzes the minor membrane lipid phosphatidylinositol 4,5-bisphosphate (PIP2), leading by an unknown mechanism to activation of the prototypical transient receptor potential (TRP) and TRP-like (TRPL) channels. We found that light exposure evoked rapid PLC-mediated contractions of the photoreceptor cells and modulated the activity of mechanosensitive channels introduced into photoreceptor cells. Furthermore, photoreceptor light responses were facilitated by membrane stretch and were inhibited by amphipaths, which alter lipid bilayer properties. These results indicate that, by cleaving PIP2, PLC generates rapid physical changes in the lipid bilayer that lead to contractions of the microvilli, and suggest that the resultant mechanical forces contribute to gating the light-sensitive channels.
CRIS-Team Scopus Importer:2020-08-12